2017
DOI: 10.1175/jcli-d-16-0532.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ozone-Depleting Substances on Tropical Upwelling, as Revealed by the Absence of Lower-Stratospheric Cooling since the Late 1990s

Abstract: The impact of ozone-depleting substances on global lower-stratospheric temperature trends is widely recognized. In the tropics, however, understanding lower-stratospheric temperature trends has proven more challenging. While the tropical lower-stratospheric cooling observed from 1979 to 1997 has been linked to tropical ozone decreases, those ozone trends cannot be of chemical origin, as active chlorine is not abundant in the tropical lower stratosphere. The 1979–97 tropical ozone trends are believed to origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
48
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 30 publications
15
48
0
Order By: Relevance
“…The role of ozone depletion in driving a decrease in AOA, shown by most of the models analysed here, has been found before (e.g. Polvani et al, 2017).…”
Section: Sensitivity Of Ozone To Ghgssupporting
confidence: 79%
“…The role of ozone depletion in driving a decrease in AOA, shown by most of the models analysed here, has been found before (e.g. Polvani et al, 2017).…”
Section: Sensitivity Of Ozone To Ghgssupporting
confidence: 79%
“…Various observation‐based studies report that despite the leveling of ozone trends [ Harris et al ., ], the stratosphere continued to cool in the 21st century and this change is generally associated with the increase of greenhouse gases [ Stolarski et al , ; Seidel et al , ]. However, the cooling of the middle and upper stratosphere has slowed down after 1997 [ Randel et al , ], whereas the trends in the lower stratosphere have become insignificantly small [ Seidel et al , ] most likely due to reversal of the trends in ozone depleting substances [ Polvani et al , ]. Our analysis of two independent CDRs suggests that the middle stratosphere (AMSU channels 10–12) has cooled in the time period 2002–2016 at an average rate of −0.14 ± 0.12 to −0.36 ± 0.14 K/decade, whereas the statistically significant change in the LS temperature is restricted to certain seasons and latitudes.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Previous studies have found that a strengthening of the BDC results in lower ozone concentrations in the tropical lower stratosphere and an increase in concentrations in the extratropics, and modeling studies have suggested that increases in GHG concentrations lead to a strengthening of the BDC Fleming et al, 2011;Garcia et al, 2008;Gillett et al, 2011;Oman et al, 2010). In contrast, a recent study by Polvani et al (2017) found that trends in ODSs, and not in GHG levels, have been the primary driver of trends in tropical upwelling. This complicates the problem of attributing ozone changes that are primarily BDC-related since both GHG and ODS forcing may be implicated in driving changes in the BDC.…”
Section: Introductionmentioning
confidence: 94%